Stressors faced by healthcare professionals and coping strategies during the early stage of the COVID-19 pandemic in Germany - Frenkel, M. O.; Pollak, K. M.; Schilling, O.; Voigt, L.; Fritzsching, B.; Wrzus, C.; Egger-Lampl, S.; Merle, U.; Weigand, M. A.; Mohr, S. (PLOS ONE, 2022)
Background: The COVID-19 pandemic has exerted great pressure on national health systems, which have aimed to ensure comprehensive healthcare at all times. Healthcare professionals working with COVID-19 patients are on the frontline and thereby confronted with enormous demands. Although early reports exist on the psychological impact of the pandemic on frontline medical staff working in Asia, little is known about its impact on healthcare professionals in other countries and across various work sectors. The present cross-sectional, online survey sought to investigate common work stressors among healthcare professionals, their psychological stress as well as coping resources during the pandemic. Methods: A sample of 575 healthcare professionals (57% male) in three different sectors (hospital, prehospital emergency care, and outpatient service) reported their experiences concerning work and private stressors, psychological stress, and coping strategies between April 17, 2020 and June 5, 2020. To capture pandemic-specific answers, most of the items were adapted or newly developed. Exploratory factor analyses (EFA) were conducted to detect underlying latent factors relating to COVID-specific work stressors. In a next step, the effects of these latent stressors across various work sectors on psychological stress (perceived stress, fatigue, and mood) were examined by means of structural equation models (SEM). To add lived experience to the findings, responses to open-ended questions about healthcare professionals` stressors, effective crisis measures and prevention, and individual coping strategies were coded inductively, and emergent themes were identified. Results: The EFA revealed that the examined work stressors can be grouped into four latent factors: "fear of transmission", "interference of workload with private life", "uncertainty/lack of knowledge", and "concerns about the team". The SEM results showed that "interference of workload with private life" represented the pivotal predictor of psychological stress. "Concerns about the team" had stress-reducing effects. The latent stressors had an equal effect on psychological stress across work sectors. On average, psychological stress levels were moderate, yet differed significantly between sectors (all p < .001); the outpatient group experienced reduced calmness and more stress than the other two sectors, while the prehospital group reported lower fatigue than the other two sectors. The prehospital group reported significantly higher concerns about the team than the hospital group (p < .001). In their reports, healthcare professionals highlighted regulations such as social distancing and the use of compulsory masks, training, experience and knowledge exchange, and social support as effective coping strategies during the pandemic. The hospital group mainly mentioned organizational measures such as visiting bans as effective crisis measures, whereas the prehospital sector most frequently named governmental measures such as contact restrictions. Conclusion: The study demonstrated the need for sector-specific crisis measures to effectively address the specific work stressors faced by the outpatient sector in particular. The results on pandemic-specific work stressors reveal that healthcare professionals might benefit from coping strategies that facilitate the utilization of social support. At the workplace, team commitment and knowledge exchange might buffer against adverse psychological stress responses. Schedules during pandemics should give healthcare workers the opportunity to interact with families and friends in ways that facilitate social support outside work. Future studies should investigate cross-sector stressors using a longitudinal design to identify both sector- and time-specific measures. Ultimately, an international comparison of stressors and measures in different sectors of healthcare systems is desirable.